Crossroads - Franzen, Jonathan (New York Farrar, Straus and Giroux, 2021)
"Crossroads is the first novel in Jonathan Franzen's A Key to All Mythologies. The trilogy tells the story of a Midwestern family across three generations, mirroring the preoccupations and dilemmas of the United States from the Vietnam War to the 2020s"--
HB
Keywords: Novels